Analisis Makna dan Nilai Moral dalam Pantun Tradisi Sekujang: Sesuaikah Menjadi Materi Pembelajaran Siswa Sekolah Dasar? - Atika Susanti; Ady Darmansyah (Eduprof : Islamic Education Journal, 2022)
Classroom learning should present material that is closest to students' lives, such as local culture. Meanwhile, local wisdom in the Sekujang tradition is a cultural heritage that must be taught to students. The purpose of this study is to describe the meaning and moral values in the traditional poetry of Sekujang; and the suitability of rhymes in the Sekujang tradition as learning materials for elementary school students. This type of research is descriptive qualitative. The subjects of this study were the traditional head and fifth grade teacher at elementary school 81 Seluma. The research instrument used by the researcher was in the form of interview guide sheets and documentation. The data analysis technique used in this study is the Miles and Huberman model. The results of this study explain that the Sekujang tradition has a rhyme that is rich in meaning and moral values. This Sekujang rhyme is appropriate if it is included in the material in elementary schools because there are basic competencies and Pantun and Character materials in Indonesian language learning and civics education Theme 6 (Cita-citaku), Sub-theme 1 (Aku dan Cita-citaku), Learning 1 Indonesian language and civics education subject. Abstrak Pembelajaran di kelas harus menghadirkan materi yang paling dekat dengan kehidupan siswa, seperti budaya setempat. Sementara itu, kearifan lokal pada tradisi Sekujang merupakan warisan budaya yang harus diajarkan kepada siswa. Tujuan penelitian ini untuk mendeskripsikan makna dan nilai moral dalam pantun tradisi Sekujang; dan kesesuaian pantun pada tradisi Sekujang menjadi materi pembelajaran siswa sekolah dasar. Jenis penelitian ini adalah kualitatif deskriptif. Subyek penelitian adalah ketua adat dan guru kelas V SDN 81 Seluma. Instrumen penelitian yang digunakan oleh peneliti berupa lembar pedoman wawancara dan dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah model Miles dan Huberman. Hasil penelitian ini menjelaskan bahwa tradisi Sekujang memiliki pantun yang kaya akan makna dan nilai moral. Pantun Sekujang ini sesuai jika dimasukan ke dalam materi di sekolah dasar karena terdapat Kompetensi Dasar (KD) dan materi Pantun dan Karakter dalam pembelajaran Bahasa Indonesia dan PPKn Tema 6 (Cita-citaku), Subtema 1 (Aku dan Cita-citaku), Pembelajaran 1 Mata Pelajaran Bahasa Indonesia dan PPKn.